Review on Deep Water Flowlines of Gumusut-Kakap, Malaysia - Koto, J. (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2016)
The Gumusut-Kakap field is located at offshore Sabah Blocks J and K at 1200 m of deep water. This paper discussed on production, gas injection and water injection flowlines of Gemusut-Kakap field development using Subsea Pro Simulation. The study was to determine wall thickness and stress and also to determine the deformation due to buckling of pipeline.